1989
DOI: 10.1113/jphysiol.1989.sp017673
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of denervation on the mechanical properties of rat and guinea‐pig skeletal muscle.

Abstract: SUMMARY1. A fast (extensor digitorum longus) and slow (soleus) twitch muscle were denervated in rats and guinea-pigs and isometric and isotonic contractions were followed for periods of up to 6 months after.2. The decay of tetanic tension with time could be described as exponential. The rate of decay of tension was greatest in rat soleus and least in guinea-pig soleus by a factor of more than three. The fast muscles atrophied at intermediate rates.3. The contraction and relaxation times of soleus and extensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…1 ( x ). The regressions of tension on time determined by Al-Amood & Lewis (1989b) are also plotted in the figure, and it is clear that the present data deviate from the extrapolation of the regression in both muscles. Indeed analysis of the present data alone showed that there was no evidence of any loss of tension in either muscle after 125 days denervation (see legend to Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 ( x ). The regressions of tension on time determined by Al-Amood & Lewis (1989b) are also plotted in the figure, and it is clear that the present data deviate from the extrapolation of the regression in both muscles. Indeed analysis of the present data alone showed that there was no evidence of any loss of tension in either muscle after 125 days denervation (see legend to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first is certainly true: EDL loses tension more slowly than soleus in the first 4 months of denervation when atrophy will be quantitatively more important than necrosis or regeneration. Al-Amood & Lewis (1989b) found that the initial tension loss in EDL was at a rate 1 6 times lower than in soleus, but this is at best only one-third of the difference required to account for the higher equilibrium tension in EDL. It may, therefore, be concluded that soleus and EDL may also differ in their rates of regeneration or necrosis.…”
Section: Denervationmentioning
confidence: 99%
See 3 more Smart Citations